Survival COVID-19 Experiences - Astrida Budiarti; Rizky Kurniasari; Dya Sustrami (Jurnal MIDPRO, 2021)
The widespread of Covid-19 has many impacts on society, especially for someone exposed to Covid-19. Covid-19 survivors have many responses starting from the beginning of being infected until they can pass the covid 19 journey phase. The purpose of this study is to explore the experiences of patients in going through the journey phase of covid 19. The research method is qualitative research with a descriptive phenomenological approach. The number of participants was 10 people determined by the Convenience Sampling method. The results showed that the initial chronology varied such as being infected from the crowd, closest family, and not knowing where the infection came from. Symptoms experienced ranging from fever, cough, anosmia, loss of sense of smell and taste, all body aches. Actions taken by participants by self-isolation, isolation in places provided by the government and some being treated in hospital. The psychological impact experienced by almost all participants felt anxiety, worry, and fear. Community responses varied starting to provide support and attention. But not all people can accept their condition, there are people who are afraid so that participants feel shunned by the community. Education about covid 19 and education on the application of health protocols, must continue to be carried out so that the incidence of covid 19 can be controlled. In addition, local government support is needed so that COVID-19 sufferers get positive support from their environment.